Political Correctness and the System of Education: Selected Examples and Consequences - Marcin Rojek (University of Lower Silesia, 2012)
This paper aims at analysing political correctness in the context of education. Political correctness has already been widely studied and commented on; however, the phenomenon has received surprisingly little attention in relation to schooling and, particularly, teachers. In the Polish system of education, political correctness is manifest first of all in the overt policy applied by people in charge of education, who refrain from using terminology of e.g. "free market," "commercial value," "product," "competition," or "profit," which could be unfavourably received or assessed by teachers. It turns out that political correctness, though founded upon proper assumptions and ideally contributing to common good, can be incorrectly understood or used for political purposes, and thus lose its initial sense, thwart communication between politicians and teachers and hinder their mutual understanding or even render it impossible. This paper attempts to reveal yet another set of conditions, this time the language-related ones, in which contemporary teachers work.